Genetic Diversity and Population Differentiation of Naked Carp (Gymnocypris przewalskii) Revealed by Cytochrome Oxidase Subunit I and D-Loop - Fang, Di-an; Luo, Hui; He, Miao; Mao, Chengcheng; Kuang, Zhen; Qi, Hongfang; Xu, Dongpo; Tan, Longfei; Li, Yuandong (Frontiers in Ecology and Evolution, 2022)
The genetic diversity in the naked carp (Gymnocypris przewalskii) of China is threatened by climate change, human activities, as well as natural factors, eliciting conservation concerns. To explore the genetic aspects of G. przewalskii, the genetic diversity, genetic structure, population differentiation, and historical demography of 566 representative individuals from seven geographically distinct ranges of Qinghai Lake were evaluated by mitochondrial DNA cytochrome oxidase subunit I (COI) and D-loop sequences. Estimates of genetic parameters showed that the seven populations of G. przewalskii had high levels of haplotype diversity (0.50243–0.94620) and low levels of nucleotide diversity (0.00079–0.00624). Haplotype genealogy indicated there was no obvious phylogenetic pattern between haplotypes. Both markers denoted the absence of population genetic structure [the genetic differentiation coefficient F-statistics (Fst) < 0] and the presence of high genetic flow (COI: 0.9731–1.0441; D-loop: 0.9480–1.0398). The mismatch between the distribution and neutrality tests supported the evidence of population expansion, which occurred during the late middle Pleistocene [COI: 0.36–0.108 MYA (Million Years Ago); D-loop: 0.497–0.165 MYA]. Furthermore, this work illustrated two simple, reliable, and inexpensive molecular markers for analysis of genetic diversity, while the sensitivity of the mitochondrial D-loop region as a reflection of genetic diversity in G. przewalskii is higher than that of the COI gene.